Molecular epidemiology of a Pseudomonas aeruginosa hospital outbreak driven by a contaminated disinfectant-soap dispenser. - Simone Lanini (Public Library of Science (PLoS), 2011)
Background and objective Pseudomonas aeruginosa infection represents a main cause of morbidity and mortality among immunocompromised patients. This study describes a fatal epidemic of P. aeruginosa that occurred in a hematology unit in Italy. Methods Retrospective cohort study, prospective surveillance, auditing, extensive testing on healthcare workers and environmental investigation were performed to define the dynamics and potential causes of transmission. RAPD, macrorestriction analyses and sequence typing were used to define relationships between P. aeruginosa isolates. Results Eighteen cases of infection were identified in the different phases of the investigation. Of these, five constitute a significant molecular cluster of infection. A P. aeruginosa strain with the same genetic fingerprint and sequence type (ST175) as clinical isolates strain was also isolated from a heavily contaminated triclosan soap dispenser. Discussion and conclusions Our results are consistent with the hypothesis that patients became indirectly infected, e.g., during central venous catheter handling through contaminated items, and that the triclosan soap dispenser acted as a common continuous source of P. aeruginosa infection. Since P. aeruginosa is intrinsically unsusceptible to triclosan, the use of triclosan-based disinfectant formulations should be avoided in those healthcare settings hosting patients at high risk of P. aeruginosa infection.